General aspects of physalis cultivation - Muniz,Janaína (2014)
The Physalis peruviana L. is an exotic fruit that belongs to the Solanaceae family with recent production in Brazil. This is presented as an alternative production with nutritional potential and economic value. The cape gooseberry plant has a high added value that can be used from its root to the fruit itself. The roots and leaves are rich in medicinal properties that are used in pharmacology. The fruit is sweet and have good content of vitamins A, C, iron, phosphorus and fiber, often used in making jellies, jams, juices and ice creams. To improve the plant canopy, but also contribute to the quality and appearance of the fruit produced some cultural practices such as staking, training systems, pruning and thinning are used. The aim of this review is to provide technical and scientific data about the culture of physalis.